Finishing diets stimulate compensatory growth: results of a study on Murray cod, Maccullochella peelii peelii - Giovanni Turchini; David Francis; S De Silva (2007)
The effective implementation of a finishing strategy (wash-out) following a grow-out phase on a vegetable oil-based diet requires a period of several weeks. However, fish performance during this final stage has received little attention. As such, in the present study the growth performance during both, the initial grow-out and the final wash-out phases, were evaluated in Murray cod (Maccullochella peelii peelii). Prior to finishing on a fish oil-based diet, fish were fed one of three diets that differed in the lipid source: fish oil, a low polyunsaturated fatty acid (PUFA) vegetable oil mix, and a high PUFA vegetable oil mix. At the end of the grow-out period the fatty acid composition of Murray cod fillets were reflective of the respective diets; whilst, during the finishing period, those differences decreased in degree and occurrence. The restoration of original fatty acid make up was more rapid in fish previously fed with the low PUFA vegetable oil diet. During the final wash-out period, fish previously fed the vegetable oil-based diets grew significantly (P < 0.05) faster (1.45 ± 0.03 and 1.43 ± 0.05, specific growth rate, % day−1) than fish continuously fed with the fish oil-based diet (1.24 ± 0.04). This study suggests that the depauperated levels of highly unsaturated fatty acids in fish previously fed vegetable oil-based diets can positively stimulate lipid metabolism and general fish metabolism, consequently promoting a growth enhancement in fish when reverted to a fish oil-based diet. This effect could be termed 'lipo-compensatory growth'.